The radical innovation investment decision refined - Natasa Bilkic; Thomas Gries; Wim A. Naudé (Institute for the Study of Labor (IZA), 2013)
We refine modelling of the radical innovation decision in this paper by extending real option theory to include non-marginal stochastic jump processes. From the model analytics we determine that the average magnitude and frequency of non-marginal stochastic jump processes are the most important parameters in this highly uncertain decision process. We show that these stochastic shocks imply that investment in radical innovation may very often be too time consuming and/or expensive to remain attractive for private entrepreneurs.
Keywords: D92; D81; L26; 330; radical innovation; innovation; entrepreneurship; investment; R&D; risk; real option theory; technology